Synthesis of sol-gel silica: optimization of supports for catalysts using orange bio-residues - Cordero, Felipe (2023)
Citrus bio-residues play an important role in obtaining different materials through the sol-gel method. This method is a friendly technique. These waste consists of organic compounds with a wide variety and chemical reactivity. In this way, it has been recognized that this kind of waste, generated mostly by the food industry, has an important potential to obtain silica to be used as a catalyst support. Provided that the principles of green chemistry and circular economy are present. This work aims to use the peel and juice of orange bio-residues, in acidic hydrolysis to obtain sol-gel silica. FT-IR spectra confirm silica formation according to the centered band at 1070 cm-1. In addition, SEM and TEM images of the synthesized materials were compared to a reference sample to contrast their morphology. Strictly speaking, orange bio-residues promote silica polymerization, due to the availability of complex organic compounds and their abundant acidic contribution.